Characterization of Contaminants Molds in Smoked Fish Coated in Chitosan - Rinto Muhammad Nur; Bahtila Hakiang; Nurafni Nurafni; Resmila Dewi (Universitas Khairun, 2021)
Smoked fish is one of the traditional fish processing through the process of open heat smoking. The water content in smoked fish is quite high. The high water content will facilitate the growth and development of decaying microbes. Some studies have reported that smoked fish after being stored for several days will be overgrown at any time, even smoked fish that have been coated with chitosan. Research objectives to analyze the characteristics of contaminants in smoked fish treated with chitosan. The research was conducted from November to December 2020 at FPIK UNIPAS Morotai Laboratory. The growth medium of the glyph uses potato extract (PDA), the isolation of the glyph from smoked cob fish, as well as the characterization of the glyph which includes macroscopic and microscopic characters. The data obtained is analyzed descriptively. The result is isolation was found five isolates of any time, namely isolates KU1, KU2, KU3, MG1, and KS1. Based on macroscopic and microscopic characterization, isolate KU1 such as Fusarium oxysporum, isolate KU2 such as Aspergillus niger, isolate KU3 such as Penicillium sp., isolate MG1 such as Aspergillus flavus, and isolate KS1 such as Acremonium sp.